The impact of corporate governance on sukuk ratings : Empirical evidence from listed companies on Bursa Malaysia 2008-2011 - Altwijry, Othman Ibrahim A (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2013)
Corporate governance is the system through which the companies are directed and managed. The essential role of corporate governance has been raised and discussed more recently due to the global financial crisis in 2007. In addition, Islamic finance industry has garnered attention in recent times because of its high growth, which among its central instruments is sukuk. Therefore, this study is conducted in order to investigate the impacts of corporate governance on sukuk ratings. This vital objective is achieved through the collecting of data from the corporations that are listed in the Bursa Malaysia from 2008 to 2011, and have issued sukuk during this period. Panel data analysis has been adopted for this study. The finding demonstrates that, separate board leadership structure, independent non-executive directors, smaller board size (at I 0% significance) as corporate governance mechanisms contribute to better and higher sukuk ratings. Meanwhile, in regard to ownership variables, lower proportion of director ownership and higher proportion of institutional ownership (at 5% significance) leads to higher sukuk ratings. Whereas in control variables, it is shown that the bigger the size of issued sukuk (at I% significance), the less years it takes to achieve maturity, with bigger firm size (at 10% significance), lower proportion of leverage, and less of net income amount, all of which contribute to better sukuk ratings. Lastly, all of these variables are found to be in line with the theoretical frameworks except for net income variable, which could be due to the nature of sukuk as a partnership and debt -based element, and it is contrary to the nature of bonds as a debt instrument. Finally, this finding is expected to contribute significantly in fields that concern regulators, issuers, investors, academicians as well as to the public.